Olefin metathesis catalysts embedded in β-barrel proteins: creating artificial metalloproteins for olefin metathesis - Sauer, Daniel F.; Schiffels, Johannes; Hayashi, Takashi; Schwaneberg, Ulrich; Okuda, Jun (Beilstein Journal of Organic Chemistry, 2018)
This review summarizes the recent progress of Grubbs–Hoveyda (GH) type olefin metathesis catalysts incorporated into the robust fold of β-barrel proteins. Anchoring strategies are discussed and challenges and opportunities in this emerging field are shown from simple small-molecule transformations over ring-opening metathesis polymerizations to in vivo olefin metathesis.
Keywords: artificial metalloprotein; β-barrel protein; metathease; olefin metathesis; ruthenium

Handbook of Metathesis - Grubbs, R. H. (Wiley-VCH, 2003)

(untitled) - Hérisson, J.-L.; Chauvin, Y. (Makromol. Chem., 1971)

(untitled) - Schrock, R. R. (Acc. Chem. Res., 1990)

(untitled) - Nguyen, S. T.; Johnson, L. K.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1992)

(untitled) - Hillmyer, M. A.; Lepetit, C.; McGrath, D. V.; Novak, B. M.; Grubbs, R. H. (Macromolecules, 1992)

(untitled) - Feast, W. J.; Harrison, D. B. (Polym. Bull., 1991)

(untitled) - Garber, S. B.; Kingsbury, J. S.; Gray, B. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Hong, S. H.; Grubbs, R. H. (J. Am. Chem. Soc., 2006)

(untitled) - Jordan, J. P.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Lin, Y. A.; Chalker, J. M.; Floyd, N.; Bernardes, G. J. L.; Davis, B. G. (J. Am. Chem. Soc., 2008)

(untitled) - Chalker, J. M.; Lin, Y. A.; Boutureira, O.; Davis, B. G. (Chem. Commun., 2009)

(untitled) - Lin, Y. A.; Chalker, J. M.; Davis, B. G. (J. Am. Chem. Soc., 2010)

(untitled) - Isarov, S. A.; Pokorski, J. K. (ACS Macro Lett., 2015)

(untitled) - Jeschek, M.; Panke, S.; Ward, T. R. (Trends Biotechnol., 2018)

(untitled) - Wilson, Y. M.; Dürrenberger, M.; Nogueira, E. S.; Ward, T. R. (J. Am. Chem. Soc., 2014)

Olefin Metathesis - Lipshutz, B. H.; Ghorai, S. (John Wiley & Sons, Inc., 2014)

(untitled) - Gawin, R.; Czarnecka, P.; Grela, K. (Tetrahedron, 2010)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Sauer, D. F.; Gotzen, S.; Okuda, J. (Org. Biomol. Chem., 2016)

(untitled) - Schwizer, F.; Okamoto, Y.; Heinisch, T.; Gu, Y.; Pellizzoni, M. M.; Lebrun, V.; Reuter, R.; Köhler, V.; Lewis, J. C.; Ward, T. R. (Chem. Rev., 2018)

(untitled) - Lewis, J. C. (ACS Catal., 2013)

(untitled) - Bos, J.; Roelfes, G. (Curr. Opin. Chem. Biol., 2014)

(untitled) - Hoarau, M.; Hureau, C.; Gras, E.; Faller, P. (Coord. Chem. Rev., 2016)

Biotechnology Set - Smith, G. M. (The Nature of Enzymes, 2008)

Biocatalysis in Organic Synthesis - Faber, K.; Fessner, W. D.; Turner, N. J. (Georg Thieme Verlag, 2015)

(untitled) - Steinreiber, J.; Ward, T. R. (Coord. Chem. Rev., 2008)

(untitled) - Wilson, M. E.; Whitesides, G. M. (J. Am. Chem. Soc., 1978)

(untitled) - Green, N. M. (Adv. Protein Chem., 1975)

(untitled) - Ward, T. R. (Acc. Chem. Res., 2011)

(untitled) - Perticaroli, S.; Nickels, J. D.; Ehlers, G.; O'Neill, H.; Zhang, Q.; Sokolov, A. P. (Soft Matter, 2013)

(untitled) - Perticaroli, S.; Nickels, J. D.; Ehlers, G.; Sokolov, A. P. (Biophys. J., 2014)

(untitled) - Fairman, J. W.; Noinaj, N.; Buchanan, S. K. (Curr. Opin. Struct. Biol., 2011)

(untitled) - Murzin, A. G.; Lesk, A. M.; Chothia, C. (J. Mol. Biol., 1994)

(untitled) - Murzin, A. G.; Lesk, A. M.; Chothia, C. (J. Mol. Biol., 1994)

(untitled) - Flower, D. R.; North, A. C. T.; Attwood, T. K. (Protein Sci., 1993)

(untitled) - De Simone, G.; Ascenzi, P.; di Masi, A.; Polticelli, F. (Biomol. Concepts, 2017)

(untitled) - Youkharibache, P.; Veretnik, S.; Li, Q.; Stanek, K. A.; Mura, C.; Bourne, P. E. (bioRxiv, Bioinf., 2018)

(untitled) - Wimley, W. C. (Curr. Opin. Struct. Biol., 2003)

(untitled) - Noinaj, N.; Gumbart, J. C.; Buchanan, S. K. (Nat. Rev. Microbiol., 2017)

(untitled) - Wierenga, R. K. (FEBS Lett., 2001)

(untitled) - Hsu, S.-T. D.; Blaser, G.; Jackson, S. E. (Chem. Soc. Rev., 2009)

(untitled) - Höcker, B.; Jürgens, C.; Wilmanns, M.; Sterner, R. (Curr. Opin. Biotechnol., 2001)

(untitled) - Tenne, S.-J.; Schwaneberg, U. (Int. J. Mol. Sci., 2012)

(untitled) - Chamoli, S.; Kumar, P.; Navani, N. K.; Verma, A. K. (Int. J. Biol. Macromol., 2016)

(untitled) - Deep, K.; Poddar, A.; Das, S. K. (Appl. Biochem. Biotechnol., 2016)

(untitled) - Lo, C.; Ringenberg, M. R.; Gnandt, D.; Wilson, Y.; Ward, T. R. (Chem. Commun., 2011)

(untitled) - Jeschek, M.; Reuter, R.; Heinisch, T.; Trindler, C.; Klehr, J.; Panke, S.; Ward, T. R. (Nature, 2016)

(untitled) - Mallin, H.; Hestericová, M.; Reuter, R.; Ward, T. R. (Nat. Protoc., 2016)

(untitled) - Bianchetti, C. M.; Blouin, G. C.; Bitto, E.; Olson, J. S.; Phillips, G. N., Jr (Proteins: Struct., Funct., Bioinf., 2010)

(untitled) - Onoda, A.; Fukumoto, K.; Arlt, M.; Bocola, M.; Schwaneberg, U.; Hayashi, T. (Chem. Commun., 2012)

(untitled) - Fukumoto, K.; Onoda, A.; Mizohata, E.; Bocola, M.; Inoue, T.; Schwaneberg, U.; Hayashi, T. (ChemCatChem, 2014)

(untitled) - Himiyama, T.; Sauer, D. F.; Onoda, A.; Spaniol, T. P.; Okuda, J.; Hayashi, T. (J. Inorg. Biochem., 2016)

(untitled) - Himiyama, T.; Taniguchi, N.; Kato, S.; Onoda, A.; Hayashi, T. (Angew. Chem., Int. Ed., 2017)

(untitled) - Onoda, A.; Kihara, Y.; Fukumoto, K.; Sano, Y.; Hayashi, T. (ACS Catal., 2014)

(untitled) - Zhang, C.; Srivastava, P.; Ellis-Guardiola, K.; Lewis, J. C. (Tetrahedron, 2014)

(untitled) - Sauer, D. F.; Himiyama, T.; Tachikawa, K.; Fukumoto, K.; Onoda, A.; Mizohata, E.; Inoue, T.; Bocola, M.; Schwaneberg, U.; Hayashi, T.; Okuda, J. (ACS Catal., 2015)

(untitled) - Boulanger, P.; le Maire, M.; Bonhivers, M.; Dubois, S.; Desmadril, M.; Letellier, L. (Biochemistry, 1996)

(untitled) - Braun, M.; Killmann, H.; Maier, E.; Benz, R.; Braun, V. (Eur. J. Biochem., 2002)

(untitled) - Philippart, F.; Arlt, M.; Gotzen, S.; Tenne, S.-J.; Bocola, M.; Chen, H.-H.; Zhu, L.; Schwaneberg, U.; Okuda, J. (Chem. – Eur. J., 2013)

(untitled) - Sauer, D. F.; Bocola, M.; Broglia, C.; Arlt, M.; Zhu, L.-L.; Brocker, M.; Schwaneberg, U.; Okuda, J. (Chem. – Asian J., 2015)

(untitled) - Matsuo, T.; Yoshida, T.; Fujii, A.; Kawahara, K.; Hirota, S. (Organometallics, 2013)

(untitled) - Grimm, A. R.; Sauer, D. F.; Davari, M. D.; Zhu, L.; Bocola, M.; Kato, S.; Onoda, A.; Hayashi, T.; Okuda, J.; Schwaneberg, U. (ACS Catal., 2018)

(untitled) - Pellizzoni, M. M.; Schwizer, F.; Wood, C. W.; Sabatino, V.; Cotelle, Y.; Matile, S.; Woolfson, D. N.; Ward, T. R. (ACS Catal., 2018)

(untitled) - Arnold, F. H. (Angew. Chem., Int. Ed., 2018)